THE CREATION OF A SUPPLEMENTARY SOFTWARE DEVICE FOR PRODUCTION MANAGEMENT IN THE DIGITALIZATION OF AGRICULTURE - Qutlimuratov Yusup Qulbaevich; Khojanova Aksungul Jenisbaevna; Kulbaeva Ulbosin Yusupovna (Journals Park Publishing, 2022)
This article discusses the development of public administration in the framework of digitalization of agriculture . There are 3 types of direction. Measures are proposed to achieve leadership between the countries in the program «Digital economy of the Republic of Uzbekistan». The expenses aimed at the implementation of the Agricultural project are presented. The principles of e-government are presented, the risks are considered and the measures of their prevention are proposed. In conclusion, the advantages of digital governance and where it will lead the country are presented.